Blockade of GCH1/BH4 Axis Activates Ferritinophagy to Mitigate the Resistance of Colorectal Cancer to Erastin-Induced Ferroptosis - Hu, Qian; Wei, Wanhui; Wu, Daiqian; Huang, Fengxing; Li, Mengting; Li, Wenjie; Yin, Jingwen; Peng, Yanan; Lu, Yuanyuan; Zhao, Qiu; Liu, Lan (Frontiers in Cell and Developmental Biology, 2022)
Ferroptosis, a cell death triggered by an overwhelming accumulation of iron-depend lipid peroxidation, possesses an excellent potential in cancer treatment. However, many colorectal cancer (CRC) cell lines are resistant to ferroptosis induced by erastin and RSL3, the classical ferroptotic inducers. And the underlying resistant mechanism remains poorly elucidated. We aim to discover the major reason of ferroptosis resistance in CRC, for better triggering ferroptosis in individualized tumor therapy. Here, we show that tetrahydrobiopterin (BH4) determines the sensitivity of CRC cells to ferroptosis induced by erastin. GTP cyclohydrolase-1 (GCH1) is the first rate-limiting enzyme of BH4. Genetical or pharmacological inhibition of GCH1 decreased BH4 and assisted erastin in cell death induction, lipid peroxidation enhancement and ferrous iron accumulation. BH4 supplementation completely abolished those ferroptotic features changed by GCH1 knockdown. Unexpectedly, GCH1 knockdown failed to enhance RSL3-induced cell death in CRC. Mechanistically, GCH1 knockdown dramatically activated ferritinophagy during erastin rather than RSL3 treatment. Administration of autophagy inhibitor reversed erastin resistance of GCH1-knockdown cells. Combining GCH1 inhibitor with erastin in vivo synergistically inhibited tumor growth in CRC. Overall, our results identified GCH1/BH4 metabolism as a burgeoning ferroptosis defense mechanism in CRC. Inhibiting GCH1/BH4 metabolism promoted erastin-induced ferroptosis through activating ferritinophagy, which suggested a novel therapeutic strategy of combining inhibitors of GCH1 with erastin in CRC.